Research on making foot pressure measuring system and determining comfort pressure of shoe upper made from knitted fabric on the forefoot of the woman’s foot - Chung, Cao Thi Kien; Huan, Bui Van (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to make the pressure measuring system including pressure measuring device and shelves. The device uses the Flexiforce A301 sensor of Tekscan USA, capable of measuring the pressure on the feet in a static and dynamic state, displaying numerical values in real time on the computer. The equipment system is easy to use, has high stability and gives reliable results, suitable for studying shoe pressure on the feet. Using this pressure measuring system to establish the relationship between comfort and pressure of shoe upper made from knitted fabric on the forefoot of the woman’s foot. 10 women without foot pathologies were selected for the study. The degree of perceived comfort of the measuring object was recorded. The pressure of 5 upper shoe material systems made from knitted fabric on the instep in 4 walking positions (phases) is measured by the pressure measuring system. The results show that the pressure value from 69.20 mmHg to 79.65 mmHg is the comfort pressure of shoe upper material on the forefoot of woman’s foot. This result is the basis for the design and selection of shoe material to ensure comfort for the user and to prevent foot injuries.